Primeiro registro de Ectopsocus titschacki Jentsch (Psocodea: Psocoptera: Ectopsocidae) para o Estado da Bahia: Uma Prova da Falta de Estudos nessa Ordem de Insecta no Brasil - Silva Neto, Alberto Moreira; Bravo, Freddy; García Aldrete, Alfonso N. (EntomoBrasilis, 2013)
Nesse trabalho realizamos o primeiro registro de Ectopsocus titschacki Jentsch para o Estado da Bahia, incluindo alguns comentários sobre a atual situação do conhecimento e da distribuição dessa ordem de Insecta no Brasil evidenciando a lacuna de conhecimento desse grupo em alguns estados especialmente aqueles pertencentes à região Nordeste. First Record of Ectopsocus titschacki Jentsch (Psocodea: Psocoptera: Ectopsocidae) in Bahia State: Proof of a Lack of Studies on this Order of Insecta in Brazil Abstract. In this paper we report the first record of Ectopsocus titschacki Jentsch for the State of Bahia, including some comments on the current state of knowledge and distribution of this order of Insecta in Brazil showing the knowledge gap that group in some states especially those belonging to Northeast.